Penerapan model pembelajaran PBL untuk meningkatkan kemampuan memecahkan masalah matematika pada siswa kelas IV SD Negeri 101 Pajalesang - Anugrah, Ainul; Firdaus, Firdaus; Sabir, Achmad (MACCA : Science-Edu Journal, 2025)
This research is classroom action research which aims to determine descriptions of teacher activities, student activities, and the ability to solve mathematical problems in applying the PBL learning model to improve the ability to solve mathematical problems in fourth grade students at SD Negeri 101 Pajalesang. The subjects in this research were all 12 fourth grade students and fourth grade homeroom teachers. Data collection techniques use observation and tests. The data analysis techniques in this research are data reduction, data presentation and drawing conclusions. The research results show that teacher activities in managing learning experienced an increase in the optimal learning process from cycle I to cycle II based on teacher activities in implementing good learning designs according to the steps of the PBL learning model to improve the ability to solve mathematical problems. Student activity in participating in the learning process increased from cycle I to cycle II based on the results of observations during the learning process using observation sheets. As for the ability to solve students mathematical problems in cycle I, there were 5 out of 12 students who completed it with an average score of 67,66 with a percentage of student learning completeness of 42% (enough), while the ability to solve students mathematical problems in cycle II there were 10 out of 12 students who achieved acomplete score with an average score of 79,91 with a percentage of student learning completeness reaching 83% (good). It can be concluded that the PBL learning model is to improve students ability to solve mathematical problems. 8